PENGEMBANGAN LEMBAR KERJA SISWA (LKS) FISIKA BERBASIS GAMBAR MATERI GETARAN DAN GELOMBANG - Suci, Devi Lara; Ahzan, Sukainil; Pangga, Dwi (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2018)
[Title: Development of Physics Student Worksheets Based on Image on Vibration and Waves Material]. Has conducted development research of media instruction in the form of Physics student worksheet (PSW) based image. This study aims to determine the eligibility of PSW based image subject matter of vibration and wave material in the class of VIII SMPN 4 Batukliang. Subjects in this study were students of class VIII SMPN 4 Batukliang the school year 2015/2016 amounting to 21 students. Methods of data collection in this study is the questionnaire. Eligibility test carried out by the validation by expert lecturers Mataram Teachers' Training College physical education and assessment by a physics teacher and students in a limited group test conducted at SMPN 4 Batukliang. The results of this development study found that the results of eligibility by expert lecturer percentage of 86.5%, then from teachers of eligibility obtained the percentage of 94%. The results based on the results of validation expert lecturers and showed a very good physics teacher. The response of the students was also very good with a percentage of 96.71% eligibility. Based on this analysis showed that the student worksheet physic-based image very decent used in the learning process.